Colorectal cancer: A review of carcinogenesis, global epidemiology, current challenges, risk factors, preventive and treatment strategies - Hossain, Md. Sanower; Hidayah, Karuniawati; Jairoun, Ammar Abdulrahman; Urbi, Zannat; Ooi, Der Jiun; John, Akbar; Lim, Ya Chee; K. M., Kaderi Kibria; A. K. M., Mohiuddin; Ming, Long Chiau; Goh, Khang Wen; Hadi, Muhammad Abdul (MDPI, 2022)
Colorectal cancer (CRC) is the second most deadly cancer. Global incidence and mortality are likely to be increased in the coming decades. Although the deaths associated with CRC are very high in high-income countries, the incidence and fatalities related to CRC are growing in developing countries too. CRC detected early is entirely curable by surgery and subsequent medications. However, the recurrence rate is high, and cancer drug resistance increases the treatment failure rate. Access to early diagnosis and treatment of CRC for survival is somewhat possible in developed countries. However, these facilities are rarely available in developing countries. Highlighting the current status of CRC, its development, risk factors, and management is crucial in creating public awareness. Therefore, in this review, we have comprehensively discussed the current global epidemiology, drug resistance, challenges, risk factors, and preventive and treatment strategies of CRC. Additionally, there is a brief discussion on the CRC development pathways and recommendations for preventing and treating CRC.